Pandemic Shock and Economic Variables Responses in ASEAN Countries Using Panel Vector Autoregressive Model - Nora Ria Retnasih; Yulia Maris Herdianti (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2023)
This quantitative research aims to measure the factors that affect the economy in 10 ASEAN countries in 2014-2020. The method used is panel vector autoregressive (PVAR). The results of the research were divided into several tests. First, the causality test shows that GDP has an effect on inflation and money supply with a one-way causality. Second, the PVAR test shows that the money supply has a significant effect on inflation and unemployment rate at lags 1 and 2. The follow-up test, namely IRF, shows that the shocks of GDP responded by all economic variables are greater than shocks to other variables. While the results of the VD test show that GDP is the largest contributor to the variation in the value of all economic variables studied, both in the short and long term.